Kritik Terhadap Konsep Eksistensi Perempuan Menurut Simone de Beauvoir Untuk Mencegah Kekerasan Terhadap Anak - Simbolon, Cahaya; Maharani, Septiana Dwiputri; Santoso, Heri; Daffa, Muhammad (Institut Filsafat dan Teknologi Kreatif Ledalero, 2025)
The role of women in caregiving, particularly for toddlers, is essential. The recent surge in cases of violence highlights that the need for proper care often remains unmet. In 2023, Databoks recorded 24,158 cases of violence against children. A common reason behind this phenomenon is the lack or absence of adequate care from parents. Economic factors, socio-cultural demands, and a lack of awareness regarding the importance of caregiving for children influence this lack of parental care. This study aims to examine the existence of women in child caregiving based on Simone de Beauvoir’s perspective as a means to prevent violence against children. The research adopts a qualitative approach, utilizing a literature review as the main method. The data sources are from credible literature, including books, journals, articles, conference proceedings, and reports. Simone de Beauvoir’s philosophical ideas are interpreted by using a hermeneutic method. The study is expected to produce a relevant and comprehensive understanding and critique of the concept of women’s existence in Simone de Beauvoir’s existentialist philosophy concerning child caregiving in order to prevent violence against children. Key words : Child Care, Existence, Human Philosophy, Women.